The origin and evolution of urban form in Wanganui East, Gonville and Castlecliff : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Geography at Massey University - Dickson, Thomas Gordon (Massey University, 1970)
The decision to study the urban form of Wanganui East, Gonville and Castlecliff (Plates 1,2 and 3) was made in 1968 after discussions with Mr. Ross, the then Town Planner for the City of Wanganui. Tho topic was chosen for two reasons. It was felt that the results could provide an insight into the evolution and nuture of the suburbs concerned, which would be of use to the City Planners. In addition it allowed for study in depth of concepts which appeared to be of considerable relevance not only to the geographer, but to the community as a whole. The three suburbs were selected because they alone within the present Borough of Wanganui had once existed as separate towns (see AppendixA), and it was thought that because of this they might exhibit distinctive characteristics in their physical form. This hypothesis appeared to be supported by a preliminary investigation of the material available. Concomitant with this assumption and resultant hypothesis was the belief that it was in any case important to examine and identify the elements of form in urban areas. It was felt that these, if investigated properly, could be helpful in correcting some of the problems inherent in the suburbs, and in New Zealand towns in general.
Keywords: Wanganui - New Zealand; Geography